Age effect on the mechanical properties of natural hydraulic and aerial lime mortars. (10th March 2020) - Garijo, Lucía; Zhang, Xiaoxin; Ruiz, Gonzalo; Ortega, José J.
Highlights: Advanced mechanical characterization of two lime mortars in the long-term. Measurement of the fracture energy and splitting tensile strength with age. Fast increase of the mechanical properties in both lime mortars up to 56 days. Empirical equations of age effect are proposed. Abstract: This paper focuses on the advanced mechanical characterization of natural hydraulic and aerial lime mortars presenting a lime/aggregate ratio of 1:3 and a water/lime ratio of 0.9. Seven properties, such as density, flexural, compressive and splitting tensile strengths, fracture energy, elastic modulus from prisms and carbonation depth by means of the phenolphthalein method, were measured at different moments. The results show that the greatest increase in the mechanical properties of both mortars occurs up to the first 56 days. This increase ranges between 60% and 90% of their corresponding value at an age of 448 days depending on the mechanical property and type of mortar. Between day 56 and day 224, there is a more moderate, but progressive evolution. However, after day 224, the evolution of the mechanical properties in light of their mean value, is very slow for the aerial lime mortar and shows a slight increase for the natural hydraulic mortar. Furthermore, various empirical equations of such behavior over time are proposed for both mortars.